The Effect of Work Environment and Job Satisfaction On Employee Performance at Assembly Section PT Mattel Indonesia In Jababeka Area I - Wahyu Wiryawan , Tri; Galih Tresnaning, Damar (Manageable, 2024)
This study aims to determine the efect of work environment and job satisfaction on employee performance at assembly section PT Mattel Indonesia in jababeka area I. This type to research uses an explanatory survey research design, which is a method to describe to causal relationship between two or more variabels through hypothesis testing. This data analysis uses multiple linear regression analysis with the help of SPSS program version 16. Based on the results of this study shows that partially the work environment and job satisfaction have an influence on employee perfomance. While simultaneously the work environment and job satisfaction have a significant influence on employee performance